Vibratory testing with the 64 Hz Rydel‐Seiffer tuning fork and its relation to the sural nerve action potential. Issue 4 (31st October 2020) - Xirou, Sophia; Kokotis, Panagiotis; Zambelis, Thomas; Anagnostou, Evangelos
Abstract: Despite its widespread use, little is known regarding the ability of the semi‐quantitative Rydel‐Seiffer tuning fork to designate peripheral nerve function. We sought to determine in a large sample of normal and abnormal nerves the relationship between vibration sense and compound sensory nerve action potential (SNAP) parameters recorded in a corresponding innervation area. Vibratory thresholds were determined on a scale of 0 to 8 with a 64 Hz Rydel‐Seiffer tuning fork placed on the lateral malleolus of 303 subjects. Sural nerve sensory neurography was employed to derive SNAP parameters, which were related to vibration sense by means of multiple linear regression. ROC curve analysis was performed to determine the classification efficacy of the tuning fork in distinguishing normal from abnormal sural nerve responses. SNAP amplitude was the most significant predictor in the whole subjects group and in the subgroup of subjects with normal SNAPs, whereas conduction velocity played a major role in subjects with abnormal SNAPs. Age was significantly associated with vibration perception, particularly in subjects with normal SNAPs. With an area under the curve of 0.730, vibration sense was a fair classifier for decreased SNAP amplitudes. The optimal vibratory cutoff was 4.2. Age is a major determinant of vibratory test results, highlighting the importance of aging of central and peripheral pathways in mediating vibration sense. Hence, neurophysiological testing cannot be omitted in the context of polyneuropathy work‐up, since even at the optimal cutoff threshold, vibratory examination still displays 40% false negative test results.